Bentuk Komunikasi Santun Petugas Rumah Sakit Terhadap Pasien di Rumah Sakit Daerah Solok Sumatera Barat: Kajian Pragmatik - Widya Fhitri; Irsyad Shabri (Jurnal Ilmiah Langue and Parole, 2023)
The aim of this study is to find out types and maxim of politeness that occurred between health workers and the patient. In conducting this reseacrh, the results obtained with the research method used is a qualitative descriptive method. In collecting the data this research used observational method, this method followed by note taking technique and the analysis method used padan pragmatics method. The result of this research shown that the news sentences occupy the top position, followed by imperative sentences. Question sentences are occurred in the third position that are often used by health workers when communicating with the patinets at Solok Regional Hospital, West Sumatera.